(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: This study aimed to evaluate hemodynamic changes and the predictive value of fluid responsiveness when gradually increasing PEEP levels in intensive care unit patients with shock. Subjects and methods: A prospective, self-controlled interventional study was conducted on 36 shock patients monitored using the PiCCO hemodynamic system from January to June 2025 at the Center for Anesthesia and Surgical Intensive Care, Viet Duc University Hospital. Results: The ROC curve demonstrated that the area under the curve of changes in cardiac index (CI) during PEEP adjustment in predicting fluid responsiveness was 0.61. The optimal cutoff for ΔCI was identified as ≥ 5.5%, with a sensitivity of 95.0%, specificity of 75.0%, and a Youden index of 0.700. In the fluid-responsive group, when PEEP was increased from 5 to 10 and then 15 cmH₂O, CI decreased from 3.14 ± 0.88 to 2.86 ± 0.76 and 2.70 ± 0.70 l/min/m², respectively; systolic blood pressure decreased from 107.3 ± 18.2 to 99.4 ± 16.6 and 95.6 ± 15.1 mmHg; mean arterial pressure dropped from 77.8 ± 10.5 to 72.1 ± 9.3 and 69.1 ± 8.6 mmHg; and central venous pressure increased from 7.4 ± 2.9 to 9.2 ± 3.0 and 10.75 ± 3.1 cmH₂O (p < 0.001). Stroke volume variation and pulse pressure variation showed a mild increase without statistical significance. In the non-responder group, hemodynamic parameters remained relatively unchanged. Conclusion: Stepwise PEEP elevation induces significant hemodynamic changes in preload-dependent patients and may serve as a supportive tool for assessing fluid responsiveness in clinical practice.